Exploring the nexus between regenerative agriculture and soil health: a special emphasis on semi-arid and arid agriculture - Arp, Jason Taylor; Sanyal, Debankur; Kaur, Jashandeep; Karki, David; Bly, Anthony (Frontiers in Agronomy, 2026)
The exploitation of natural resources used in food production systems, including productive soils, has occurred due to intensive and degenerative agricultural practices aiming at food security. These degenerative practices have pronounced effects on arid and semi-arid ecosystems, increasing rates of soil degradation in productive agricultural regions throughout the world. The idea of regenerative agriculture (RA) started in the 1980s, defined as a system that moves beyond sustainability in an attempt to actively improve resources through production practices. These practices include approaches like reduced tillage intensity, cover crops, crop rotation, and livestock integration, which are globally recognized as soil health practices (SHPs). Information regarding the efficacy and barriers to the adoption of SHPs in dryland agricultural systems is sparse. In this article, literature is compiled and reviewed to assess the feasibility of prominent SHPs in dryland systems, with special focus on the arid and semi-arid systems. Extensive research has shown that SHPs potentially improve soil physical, chemical, and biological properties; however, reports of potential obstacles like yield loss, lack of short- and medium-term economic gains, and inaccessibility of proper equipment are preventing a smooth transition to regenerative systems. The success of RA practices varies depending on the dominant cash crop type, geographical region, whether the practices are used in tandem with one another, and socioeconomic factors. The extreme weather and water scarcity of dryland systems make it challenging to integrate RA practices effectively. Furthermore, the adoption of RA practices in large-scale commercial agriculture often hinges on economic variables like the cost of new machinery and the labor costs to implement the new practices. Here, the outcomes of SHPs are reviewed to clarify existing knowledge to enhance RA adoption for providing food security in a cost-effective, environmentally safe, and sustainable way while stabilizing the farm economy through increasing the profits of farms and diversifying farm incomes.